Profile of Motoric and Non-Motoric Symptoms Using the Indonesian Version of the Wearing-Off Questionnaire-19 in Parkinson’s Patients - Bernadetha Muktiarini; Rizaldy Taslim Pinzon; Yacobus Christian Prasetyo (Universitas Airlangga, 2025)
Highlight: Tremors are the most common motor symptom in patients with Parkinson's disease. Abdominal discomfort is a prevalent non-motor symptom of Parkinson's disease. Comprehensive symptom management is essential for patients with Parkinson's disease. ABSTRACT Introduction: Parkinson's disease is a neurodegenerative disorder characterized by motor and non-motor symptoms. The prolonged administration of levodopa in patients may induce the wearing-off phenomenon, where symptoms recur before the next dose. Studies on the symptom profile of Parkinson's disease, especially in wearing-off conditions, are crucial for further management. Objective: This study aimed to determine the motor and non-motor symptom profile of patients with Parkinson's disease. Methods: conducted. The Indonesian version of the Wearing-Off Questionnaire-19 (WOQ-19) was used to identify motor and non-motor symptoms. Data were collected from 30 Parkinson’s patients at Bethesda Yogyakarta Hospital from October to December 2023 using a purposive sampling technique. The sample size was calculated using OpenEpi V3.01. Results: The most prevalent motor symptom among patients with Parkinson's disease was tremor (100%), followed by bradykinesia (93.33%) and rigidity (86.67%). The most common non-motor symptoms reported were abdominal discomfort (56.67%) and body aches (50%). Conclusion:Patients have a variety of Parkinson's disease symptoms. Parkinson's patients most commonly experienced motor symptoms such as tremors, bradykinesia, and rigidity, along with non-motor symptoms like abdominal discomfort and body aches. The significant percentage of wearing-off seen in this study underscores its common occurrence and highlights the importance of early identification and management.